Internal devaluation and labor market outcomes: Evidence from Latvia - Hartmut Lehmann; Tiziano Razzolini; Anzelika Zaiceva (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
This paper analyzes the policy response and labor market adjustment of Latvia, which faced the most severe recession in Europe and globally. Latvia's adjustment and recovery from the 2008 economic crisis represents "a rare case study", which "has been an object of intense attention" (Blanchard et al., 2013) as country's authorities, despite many experts' recommendations, decided to maintain its currency peg and adjust through fiscal austerity and internal devaluation implementing major structural reforms. Three years later Latvia returned to a positive growth path and in 2014 joined the Euro zone. The main question in the literature is whether this adjustment represents a success story and can provide a lesson for other countries in the Euro area. We provide details on the adjustment in the Latvian labor market employing individual level data over the years 2002 to 2012. We show that with flexible labor markets, weak unions and relatively low employment protection, adjustment takes place predominantly at the extensive margin since it is driven by flows from permanent wage employment to unemployment. Underemployment constitutes another important adjustment channel, while the evidence for informal employment is more mixed. Wage regressions suggest that job mobility is not associated with increased labor productivity during and immediately after the crisis. We also identify groups particularly affected by the crisis and provide suggestions for the right mix of policy interventions.
Keywords: J6; J21; P16; 330; Unemployment; labor market flows; Latvia; crisis